Incident obstructive sleep apnea in patients with primary aldosteronism following COVID-19 infection: a health global federated network analysis - Wen-Kai Chu; Chih-Cheng Lai; Tai-Shuan Lai; Yen-Hung Lin; Vin-Cent Wu (Therapeutic Advances in Chronic Disease)
Background: In the context of the COVID-19 pandemic, there is growing concern about the virus’s effects on individuals with existing endocrine disorders such as primary aldosteronism (PA). Objectives: This study explores the potential relationship between PA and the risk of developing obstructive sleep apnea (OSA) after a COVID-19 infection. Design: In this retrospective cohort study, we utilized data from the TriNetX database, covering the period from January 2019 to January 2023. We identified essential hypertension (EH) patients as the control group, employing 1:1 propensity score matching. Methods: The endpoints included incident OSA and all-cause mortality. Results: Among 11,422,001 patients with PCR-positive COVID-19, we identified 3628 PA patients (mean 63.1 years, male 38.1%). After a median follow-up of 1.9 years, the rate of OSA was 28.9 per 1000 person-years in PA patients compared to EH with 16.7. We showed a significant increase in incident OSA (adjusted hazard ratio (aHR) 1.58, p  < 0.001) and mortality (aHR 1.12, p  = 0.04) in PA patients than EH post-COVID-19. The horizon plot revealed that patients with pre-existing PA had the highest risk of OSA at 2 months (aHR = 2.34) post-COVID-19. In subgroup analysis, PA patients with a high body mass index (⩾30 kg/m 2 ; aHR 1.81, p  = 0.001) or preserved kidney function (aHR 2.00, p  < 0.001) had increased OSA incidences post-COVID-19. Conclusion: Our study underscores a notable rise in incident OSA among PA patients post-COVID-19, highlighting the imperative for diligent OSA screening, particularly among individuals with obesity or preserved kidney function.